Penguatan Keagamaan Melalui Literasi Digital: Implementasi Metode DIROSA dalam Pemberantasan Buta Al-Qur’an di Desa Taruban Wetan Kulon Progo - Primaningtyas, Mega; Arifin, Zaenal; Kusuma, Alam Budi (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2025)
The advancement of digital technology opens up great opportunities to improve religious literacy among the community. The background of this program is that many adults and elderly individuals are still unable to read the Qur’an properly and correctly. The implementation method was carried out four times per week with a 45-minute duration for each meeting using a classical (group-based) approach. This community service activity aims to eradicate Qur’anic illiteracy among adults in Taruban Wetan Village through the application of the DIROSA Method (Adult Learning of the Qur’an) supported by digital literacy. The method applied was a participatory approach through the stages of socialization, training, and mentoring by utilizing digital learning media for Qur’anic education. The results of the program showed a significant improvement in participants’ ability to read the Qur’an, as well as increasing awareness of the use of technology in religious learning. The integration of digital literacy in Qur’anic learning has proven effective in strengthening the community’s religious competence while simultaneously enhancing human resource capacity in the digital era.